CONTENT AND EVALUATION OF INNOVATIVE COMPONENTS OF HUMAN POTENTIAL IN THE RATINGS OF UNIVERSITIES - Davydova, Tatiana; Barkalov, Sergey; Poryadina, Vera (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The aim of the research is to study the content of the innovation component of human potential in the rankings of universities, its assessment through the prism of the educational environment and its individual elements. The article considers the innovation component of human potential from the standpoint of its importance on the scale of the fourth industrial revolution. The research focuses on the formation, development and realization of human potential in the system of higher education. The analysis of global, national, regional ratings of the performance of universities is presented. Ratings are abstracted from nationality and classified by target and structural features. The ratings are classified according to the target and structural features. Features of the content and evaluation of human potential and its innovative component in the structure of ratings of various groups are revealed. The directions for improving the rating structure are identified, taking into account the essential importance of the innovative component of human potential for the modern economy. The characteristics of the structure of the rating allowing estimating the innovative component of human potential is given. An innovative component of the rating of universities was developed. A list of indicators was synthesized, which is the basis for the implementation of the rating assessment of the innovation component of human potential. Using the method of mathematical modeling developed an innovative component of the ranking of universities.